Amendments of January 2018 to the Act on the Institute of National Remembrance - Commission for the Prosecution of Crimes against the Polish Nation in Light of International Law (Polish Yearbook of International Law, 2017)
This article analyses the amendments of January 2018 to the Act on the Institute of National Remembrance (INR) of 1998, which has raised doubtsinlight ofinternational law and provoked diplomatic tensions betweenPoland onone side and Germany, Ukraine, United States of America and Israel on the other. The INR is a national institution whose role is, among others, to prosecute perpetrators of international crimes committed between 19171990. The article proves that the wording of the amendments is inconsistent with international law, as it ignores the principles of international responsibility, defnitions of international crimes, and disproportionately limits freedom of expression. In consequence, it cannot be expected that third states will cooperate with Poland in the execution of responsibility for violation of the newly adopted norms.